Active Mode Switching Control Strategy of Hybrid Electric Vehicle based on Identification of Road Gradient - Ming Ye; Xiangyu Gongye; Zhihong Zhu; Wenlei Wei (Jixie chuandong)
In order to study the control strategy of active mode switching for single shaft parallel hybrid electric vehicles based on identification of road gradient, the numerical model of hybrid electric vehicle and road gradient model are built on the Matlab. On the basis of road gradient identification，the speed and demand torque of hybrid electric power system at the next time are predicted by the simulation model. The working mode of hybrid electric vehicle is determined according to the required torque and the SOC of the battery at the current time and the next time. On the basis of determining the working mode first，taking the minimum fuel consumption as the objective function，the optimal torque allocation is carried out in real time with dynamic programming algorithm. On the premise of economy，the hybrid power system can achieve the shift gear at the uphill moment to meet the needs of driver's power performance and drivability.